Świętość w czasach podbojów islamskich. Męczennicy chrześcijańscy z Gazy z VII wieku - Paczkowski, Mieczysław Celestyn (Vox Patrum, 2016)
The article focuses the story of the martyrdom of 60 Christian soldiers in Gaza who were executed for their refusal to convert to Islam during the Muslim invasion of Palestine. It is a final episode of varied Christian history of that region. Christian history of Gaza appears as complex and fascinating. In this region in the 4th century paganism was still strong but the monastic life developed in the vicinity of Gaza. Literary sources annotated the anti-Chalcedonian resistance of monastic circles in the wake of the council of Chalcedon. Christian history of the Gaza region ended dramatically with the Arab conquest in the 7th century. Just at that time a group of Christian soldiers refused the offer of the commander of the winners Muslims. The narrative of their martyrdom was preserved in a Latin translation of a Greek original. According to the text of the Passio, the Christian soldiers were executed in two groups: at Jerusalem and at Eleutheropolis. Bishop Sophronius of Jerusalem intervened in favor of these Martyrs and comforted them. He also gained the palm of martyrdom. The Passio in two different Latin recensions reveals a relatively neglected aspect in the history of the Holy Land during the period of heightened religious tension.